2022
DOI: 10.1002/ejhf.2654
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics and 1‐year outcomes in hospitalized patients with heart failure with preserved ejection fraction: results from the China Cardiovascular Association Database‐Heart Failure Center Registry

Abstract: Aim We aimed to evaluate clinical characteristics and 1‐year outcomes in hospitalized patients with heart failure with preserved ejection fraction (HFpEF) from China. Factors associated with outcomes (hospitalization for HF [HHF] and cardiovascular [CV] death) were assessed. Method and results Data were from the China Cardiovascular Association (CCA) Database‐HF Center Registry. Between January 2017 and June 2021, 41 708 hospitalized HFpEF patients with 1‐year follow‐up from 481 CCA Database‐HF Center certifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 45 publications
(129 reference statements)
1
16
0
Order By: Relevance
“…Successful risk strati cation is a key to enhancing clinical care in HFpEF (23). A prospective study from China, which included 41708 hospitalized HFpEF patients, reported that the 1-year rate of cardiovascular death was 3.1% with the most common comorbidities of hypertension, coronary heart disease and AF (24), which is similar to our study ndings. An analysis of the ESC Heart Failure Long-Term Registry associated the increased hazard with baseline characteristics such as age, NYHA class, pulmonary congestion, aortic stenosis, AF, peripheral artery disease and chronic kidney disease (25).…”
Section: Discussionsupporting
confidence: 88%
“…Successful risk strati cation is a key to enhancing clinical care in HFpEF (23). A prospective study from China, which included 41708 hospitalized HFpEF patients, reported that the 1-year rate of cardiovascular death was 3.1% with the most common comorbidities of hypertension, coronary heart disease and AF (24), which is similar to our study ndings. An analysis of the ESC Heart Failure Long-Term Registry associated the increased hazard with baseline characteristics such as age, NYHA class, pulmonary congestion, aortic stenosis, AF, peripheral artery disease and chronic kidney disease (25).…”
Section: Discussionsupporting
confidence: 88%
“…Mitochondrial dysfunction in HF with preserved ejection fraction (HFpEF): In the community, HF with preserved ejection fraction (HFpEF) accounts for approximately half of the global HF cases, and the prevalence of HF is increasing in the aging population [ 51 ]. AFs were among the three most common precipitating factors for hospitalizations and the most common comorbidities in those patients with HFpEF [ 52 ]. Main risk factors for HFpEF are obesity, metabolic syndrome, and diabetes [ 53 ].…”
Section: Energy Metabolism In the Heartmentioning
confidence: 99%
“…Patients were often burdened by multiple comorbidities, namely hypertension, atrial fibrillation and coronary artery disease (CAD). At 1‐year follow‐up, rehospitalization due to HF occurred in 13.6% of patients, while cardiovascular death in 3.1% 3 …”
Section: Epidemiologymentioning
confidence: 99%
“…At 1-year follow-up, rehospitalization due to HF occurred in 13.6% of patients, while cardiovascular death in 3.1%. 3 The relationship between quality of care as assessed using the European Society of Cardiology (ESC) quality indicators (QIs) and outcome was investigated among 43 704 patients with HF from the Swedish HF registry. 4,5 Out of the 16 QIs, 13 could be measured and 5 were inversely associated with all-cause mortality during follow-up.…”
mentioning
confidence: 99%